EFFECT OF HEALOL OIL ON WOUND HEALING IN WISTAR RATS: A NOVEL STUDY - V, Sujith; G, Poornima; O, Balaji; Kl, Bairy; E, Praveen S; N, Somayaji (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Wound healing is a complex process, and various plant extracts have been used to study the effect of medicinal plants on wound healing. Healol oil is used in some tribal areas for ulcer healing and treatment of burn wounds. There are no animal studies done so far using healol oil to find out its role in the treatment of wounds. Hence, the aim of our study is to find the effect of healol oil in excision as well burn wounds in Wistar rats. Methods: Thirty-six Wistar rats were used, 18 rats in excision wound model and remaining in burn wound model. Each model consists of three groups of six rats each. Povidone-iodine was used as a standard control in excision wound model and silver sulfadiazine was used as a standard control in burn wound model. Healol oil was used as test drug in both the models. Period of epithelization and wound contracture rates were analyzed. Histopathological analysis of the skin tissue was done. One-way analysis of variance was used followed by Tukey's post hoc test for statistical analysis using SPSS version 23 software, P value of <0.05 was taken as statistical significance. Results: Both standard and test groups showed significantly faster wound healing (p<0.001) compared to control rats treated with paraffin wax in both the models. In excision model standard povidone was significantly (p<0.001) better compared to healol oil whereas in burn model, silver sulfadiazine and healol oil showed comparable results with respect to period of epithelization without statistical significance (p>0.05). Conclusion: Wound healing property of healol oil is proved, and further clinical trial can be done to find out the effect of healol oil on chronic wounds due to various etiologies.